Study of Minimum Service Standard Index in Public Transportation: Sample of Trans Pakuan Bogor - Octadian Pratiwanggono; Rima Febrina (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Public transportation in Bogor City is one of the issues that is still a concern and needs to be studied. Urban transportation management involves many strategic aspects and issues, such as reducing gas emissions, multimodal integration, and increasing public awareness and convenience to change the habits for using mass transportation. Buy the service program from BPTJ Ministry of Transportation through Trans Pakuan has been operating since November 2021 and during the operational period studies are still needed to achieve and improve service standards. This study uses field survey methods and quantitative analysis of the 8 dimensions of minimum service standards for mass transportation. The result shows that the Public Perception Service Index (Trans-Pakuan) shows "good" conditions in each corridor. However, the Trans Pakuan operation is considered ineffective because the loading factor is dominated by students, not workers. There are still 61.6% distance from bus stops above 1 kilometer with travel time to the bus stop taking more than 10 minutes by 56.9%. Trans-Pakuan BTS users are expected to be shifted to communities with a higher economic level by conducting in-depth studies to find out the expectations of public transport standards desired by middle income to higher income.